DEVELOPMENT CONSTRUCTIVE DESIGN THROUGH COLLABORATION LEARNING STRATEGIES CAN TO IMPROVE QUALITY ON THE COLLEGE OF SERIES PUBLISHING MANAGEMENT - Sokhibul Ansor; Inawati Inawati (Edulib, 2020)
The emergence of a new paradigm is expected to contribute to overcoming the problem of learning, namely students will increase the knowledge, skills, and attitudes of people who learn. For students to experience changes in learning, a teacher, lecturer, and instructor are seen as needing to develop a constructivist-based learning design. The aim of developing constructivist learning designs through collaborative learning is to produce learning designs in the course management series publications. With this learning design, it is expected. (1) Students actively construct or build their knowledge; (2) Students are free in learning and doing collaborative activities in learning, (3) Provides opportunities for students to use diverse learning resources, (4) Students are encouraged to solve problems in learning. The learning strategy used in the management course for serial publications is collaborative learning. The research method used in the development to produce this design product is the R2D2 model. The results show that the collaborative learning strategy was tested on the subject matter of making a catalog of serial publications which shows that 5 respondent groups declared to be very feasible do not need to be revised in making software programs for serial publications of catalogs; 5 groups of respondents declared eligible do not need to be revised